DESIGNING A FRAMEWORK FOR CULTIVATING THE LOGICAL AND PSYCHOLOGICAL THINKING SKILLS OF CHESS LEARNERS. (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The variety of approaches to the concept of "Logical thinking" and their controversy allow us to offer our own version. In our opinion, logical thinking is an actual psychological-pedagogical and social activity in the process of educational and practical activities aimed at applying various consciously reasonable logical operations in one's activity, creating hypotheses and evaluating the results according to the laws of logic, and using these skills is a systematic formative mental characteristic of a person based on a complex mechanism in solving cultural problems.